Footprint Tracker: Supporting Diary studies with lifelogging - Gouveia, Rúben; Karapanos, Evangelos (My University, 2013)
As HCI shifts "to the wild", in-situ methods such as Diary Methods and the Experience Sampling Method are gaining momentum. However, researchers have acknowledged the intrusiveness and lack of realism in these methods and have proposed solutions, notably through lightweight and rich media capture. In this paper we explore the concept of lifelogging as an alternative solution to these two challenges. We describe Footprint Tracker, a tool that allows the review of lifelogs with the aim to support recall and reflection over daily activities and experiences. In a field trial, we study how four different types of cues, namely visual, location, temporal and social context, trigger memories of recent events and associated emotions. We conclude with a number of implications for the design of lifelogging systems that support recall and reflection upon recent events as well as ones lying further in our past.
Keywords: Diary methods; Experience sampling; Lifelogging